Investing In Gold In Times Of Global Crisis - Rudiansyah Anggara (International Asia Of Law and Money Laundering, 2022)
Investment is placing capital or funds in an asset that is expected to provide results or increase in value in the future. Every investment applies the law the higher the return offered, the higher the risk that must be borne by the investor. So the investor could have suffered losses even more than it could have lost all its capital. Among the various investment instruments, gold precious metal is an investment option with a safe category, as an alternative to investing in the midst of a global crisis.